Surgical replacement of iatrogenically prolapsed penis in a dromedary camel - S.A.T. Al-Qubati; M.N. Telfah; M.I. Siddiqui (Open Veterinary Journal, 2012)
Prolapse of the penis through an iatrogenic incision on the right side of the preputial base in a five year old dromedary camel was handled surgically and the organ was successfully replaced into the preputial cavity. The condition occurred as a result of draining an abscess at the base of the prepuce by a quack about eight months earlier. The reason to report this case lies in its peculiarity that although the penis remained outside the preputial cavity for about eight months exposed to the external environment, yet no complications pertaining to its fragile tissue and urination occurred during this long period as seen in cases of paraphimosis.